An Automated Canine Line-Up for Detection Dog Research - Aviles-Rosa, Edgar O.; Gallegos, Shawna F.; Prada-Tiedemann, Paola A.; Hall, Nathaniel J. (Frontiers in Veterinary Science, 2021)
Currently there is a need to develop technology that facilitates and improves detection dog research. The aim of this research was to develop an automated computer-driven olfactory line-up task. The apparatus consisted of three olfactometers. Each olfactometer was equipped with flow meters to regulate air flow and dilution, and 6 solenoid valves connected to odor jars. Each olfactometer generated an odor, and this was carried to an odor port where the dogs sample it. The olfactometer’s valves were activated by a microcontroller and a Python program was built to control each olfactometer and randomize and balance the odor presentation. Dogs (N = 12) received one or two 40-trial training session in a day where they progressed through a series of training phases where they learned to detect and alert to double-base smokeless powder (SP). An alert consisted of a 4s nose hold. This was measured by infrared sensors in the ports. For each trial, the apparatus recorded dogs’ search latency, sniff time, port entries, and response. All this information was automatically recorded in a csv file. A photo ionization detector (PID) and SPME GC/MS were used to evaluate the odor dynamics and to instrumentally verify odor presence and clearance. A control test was conducted at the end of training to ensure dogs were alerting exclusively to the odorant. All twelve dogs readily learned to operate the apparatus within 23 days, and all exceeded 85 % accuracy. Control tests indicated dogs were leveraging only olfactory cues and not unintentional cues such as auditory cues from the apparatus. Analytical data showed that odor was detected in the port immediately after the activation of a valve and that odor clearance occurred immediately after the valve was closed. The apparatus developed was easy to operate by the dogs and allowed substantial data collection using double-blind testing procedures in a very short period at an affordable cost point for research equipment (~$5,000 USD). The apparatus may prove to be a useful research tool to provide optimal odor stimuli control, ensure double-blind conditions, reduce labor, and significantly increases the amount of data collected.